Factors and Reasons Associated with Hesitating to Seek Care for Migraine: Results of the OVERCOME (US) Study - Robert E. Shapiro; Eva Jolanda Muenzel; Robert A. Nicholson; Anthony J. Zagar; Michael L. Reed; Dawn C. Buse; Susan Hutchinson; Sait Ashina; Eric M. Pearlman; Richard B. Lipton (Neurology and Therapy)
Abstract Introduction Despite a variety of available treatment options for migraine, many people with migraine do not seek medical care, thereby reducing opportunities for diagnosis and effective treatment and potentially leading to missed opportunities to reduce the burden of disease. Understanding why people hesitate to seek care for migraine may help healthcare professionals and advocates address barriers and improve outcomes. The aim of this study, in a large adult population sample in the United States (US), was to identify factors associated with and reasons for hesitating to seek healthcare for migraine. Methods The web-based OVERCOME (US) survey study identified adults with active migraine in a demographically representative US sample who answered questions about hesitating to seek care from a healthcare provider for migraine and reasons for hesitating. Supervised machine learning (random forest, least absolute shrinkage and selection operator) identified factors associated with hesitation; logistic regression models assessed association of factors on hesitation. Results The study results show that of the 58,403 participants with active migraine who completed the OVERCOME (US) baseline survey and provided responses to the question on hesitating to seek care for migraine, 45.1% (n = 26,330/58,403) with migraine indicated that they had ever hesitated to seek care for migraine. Factors most associated with hesitating to seek care were hiding migraine (odds ratio [OR] = 2.69; 95% confidence interval [CI]: 2.50, 2.89), experiencing migraine-related stigma (OR = 2.13; 95% CI 1.95, 2.33), higher migraine-related disability (OR = 1.30; 95% CI 1.23, 1.38), and higher ictal cutaneous allodynia (OR = 1.26; 95% CI 1.19, 1.35). The most common reasons participants stated for hesitating included (1) 44.2% wanting to try and take care of migraine on their own, (2) 33.8% feeling that their migraine or headache would not be taken seriously, (3) 29.2% thinking that their migraine was not serious/painful enough, and (4) 27.4% not being able to afford it or not wanting to spend the money. The main limitation of the study includes the requirement for respondents to have internet, access which may have reflected cohort bias, and the quota sampling rather than random sampling to create a demographically representative sample. Conclusions Hesitating to seek migraine care is common and is most strongly associated with hiding the disease and migraine-related stigma. Those experiencing higher migraine-related burden are more hesitant to seek the care that might alleviate the burden. These findings suggest that migraine’s social context (e.g., stigma) is a major determinant of hesitance to seek migraine care.